Lightweight, Flexible Cellulose-Derived Carbon Aerogel@Reduced Graphene Oxide/PDMS Composites with Outstanding EMI Shielding Performances and Excellent Thermal Conductivities - Song, Ping; Liu, Bei; Liang, Chaobo; Ruan, Kunpeng; Qiu, Hua; Ma, Zhonglei; Guo, Yongqiang; Gu, Junwei (Nano-Micro Letters, 2021)
In order to ensure the operational reliability and information security of sophisticated electronic components and to protect human health, efficient electromagnetic interference (EMI) shielding materials are required to attenuate electromagnetic wave energy. In this work, the cellulose solution is obtained by dissolving cotton through hydrogen bond driving self-assembly using sodium hydroxide (NaOH)/urea solution, and cellulose aerogels (CA) are prepared by gelation and freeze-drying. Then, the cellulose carbon aerogel@reduced graphene oxide aerogels (CCA@rGO) are prepared by vacuum impregnation, freeze-drying followed by thermal annealing, and finally, the CCA@rGO/polydimethylsiloxane (PDMS) EMI shielding composites are prepared by backfilling with PDMS. Owing to skin-core structure of CCA@rGO, the complete three-dimensional (3D) double-layer conductive network can be successfully constructed. When the loading of CCA@rGO is 3.05 wt%, CCA@rGO/PDMS EMI shielding composites have an excellent EMI shielding effectiveness (EMI SE) of 51 dB, which is 3.9 times higher than that of the co-blended CCA/rGO/PDMS EMI shielding composites (13 dB) with the same loading of fillers. At this time, the CCA@rGO/PDMS EMI shielding composites have excellent thermal stability (THRI of 178.3 °C) and good thermal conductivity coefficient (λ of 0.65 W m-1 K-1). Excellent comprehensive performance makes CCA@rGO/PDMS EMI shielding composites great prospect for applications in lightweight, flexible EMI shielding composites. Highlights: 1 Cellulose aerogels were prepared by hydrogen bonding driven self-assembly, gelation and freeze-drying. 2 The skin-core structure of CCA@rGO aerogels can form a perfect three-dimensional bilayer conductive network. 3 Outstanding EMI SE (51 dB) is achieved with 3.05 wt% CCA@rGO, which is 3.9 times higher than that of the co-blended composites.